2022
DOI: 10.1186/s13073-022-01125-8
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps have auto-catabolic activity and produce mononucleosome-associated circulating DNA

Abstract: Background As circulating DNA (cirDNA) is mainly detected as mononucleosome-associated circulating DNA (mono-N cirDNA) in blood, apoptosis has until now been considered as the main source of cirDNA. The mechanism of cirDNA release into the circulation, however, is still not fully understood. This work addresses that knowledge gap, working from the postulate that neutrophil extracellular traps (NET) may be a source of cirDNA, and by investigating whether NET may directly produce mono-N cirDNA. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 92 publications
1
17
0
Order By: Relevance
“…These fragments could be distinguished by a shorter length distribution (peaking at 900-4300bp or 5-25 nucleosomes) and had end motif patterns consistent with typical DNASE1L3 fragmentation. The length distribution observed in these cancers is broadly consistent with that of Neutrophil Extracellular Traps (NETs) exposed to circulating nucleases [36], suggesting they might derive from NETs fragmented in circulation. NETs have been associated with myeloid hyperproliferation [37] and linked to accumulation of total circulating DNA in cancer [38,39].…”
Section: Discussionsupporting
confidence: 58%
“…These fragments could be distinguished by a shorter length distribution (peaking at 900-4300bp or 5-25 nucleosomes) and had end motif patterns consistent with typical DNASE1L3 fragmentation. The length distribution observed in these cancers is broadly consistent with that of Neutrophil Extracellular Traps (NETs) exposed to circulating nucleases [36], suggesting they might derive from NETs fragmented in circulation. NETs have been associated with myeloid hyperproliferation [37] and linked to accumulation of total circulating DNA in cancer [38,39].…”
Section: Discussionsupporting
confidence: 58%
“…We previously validated the use of a set of markers, consisting of two protein markers (NE and MPO) and cir-nDNA concentrations, to indirectly quantify NETs formation in metastatic colorectal cancer 25 , 26 and in COVID-19 26 , 27 patients. First, we demonstrated that the quantitative analysis of cir-nDNA empowers the assessment of NETs formation when combined with the quantification of the granular enzymes (NE and MPO) that are essential in NETs production and in the digestion of trapped microbes.…”
Section: Introductionmentioning
confidence: 99%
“…First, we demonstrated that the quantitative analysis of cir-nDNA empowers the assessment of NETs formation when combined with the quantification of the granular enzymes (NE and MPO) that are essential in NETs production and in the digestion of trapped microbes. 25 , 26 Second, we have recently demonstrated that the degradation of NETs’ chromatin fibers are degraded by DNases in blood and could be autocatalytic, leading to DNA fragmentation, thus producing mainly mono-nucleosomes as well as a very small proportion of di-nucleosomes. 26 Several studies showed that plasma-extracted DNA is mainly associated with mono-nucleosomes and to a lesser extent di-nucleosomes (>90% in healthy individuals).…”
Section: Introductionmentioning
confidence: 99%
“…cir-mtDNA may cause an inflammatory response by acting as damage-associated molecular patterns, in combination with other circulating NETs by-products (histones, granule proteins like NE or MPO, and structural proteins). Although HI have lower amounts of cir-mtDNA than cir-nDNA, cir-mtDNA could be a marker for inflammatory diseases [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%